Os cuidados promovidos ao recém-nascido no ambiente hospitalar de três regionais de saúde que integram a Rede Mãe Paranaense - Grebinski, Ana Tamara Kolecha Giordani (2019)
Introduction: The importance of women, newborns and family members receiving adequate care during pregnancy, childbirth, puerperium and neonatal period is emphasized. Guiding care with a set of actions in health promotion, is fundamental for Rede Mãe Paranaense, as well as promoting health care at all levels of care. But in the hospital environment where care is focused on curing the disease, encourage Health promotion is to ensure a quality of care. Objective: To analyze the profile of puerperal women and newborns attended at hospitals of three Regional Health Centers of the state of Paraná, Brazil, and to evaluate the support and support for newborn care in a hospital environment. Methodology: Descriptive study of quantitative nature that was developed in municipalities of three Health Regions (RS): 9th RS of Foz do Iguaçu, 10th RS of Cascavel and 17th RS of Londrina, Paraná, southern Brazil. Data collection was performed by means of a structured instrument, which took place in 2017 between March and July, and was performed by fourth-year nursing students. Quantitative data were analyzed using the Student's t-test with 95% reliability, and for the qualitative variables, the chi-square test or Fisher's exact test was performed. Results: The three health regions totaled 1270 interviews, 397 in the 9th RS, 385 in the 10th RS and 488 in the 17th RS. Among the questions about support and help to perform the first care with the NB (p=0.000) the highest affirmative rate was in the 9th with 92.4% (367), followed by the 10th with 87.0% (335) and last 17th with 79.5% (388). Regarding which professional who helped, all regionals indicated as Nurse or Nursing Resident, being 92.4% (339) in the 9th RS, 88.1% (297) in the 10th RS and 82.3% (325) in the 17th Regional. Baby bathing (p=0.000) for mothers can be a stressful and delicate task, but the responses were positive, 90.7% (360) in the 9th RS, 77.7% (299), in the 10th RS and 73.4%. (358) on the 17th RS indicated that they received help. Regarding the hygiene of the umbilical stump there was a statistical difference between the regional (p=0.000), in the 9th RS, with 91.1% (358); in the 10th RS, with 81.3% (313); and in the 17th RS, with 77.5% (378) of the mothers mentioned that they received help. Regarding perineal hygiene and diaper change (p=0.000), bladder (p=0.000) and intestinal elimination of the baby (p=0.000), there was a statistical difference between the regional ones, such care also obtained affirmative answers. Regarding breastfeeding, the mothers said they received some support or help from a professional, obtaining 90.4% (359) in the 9th RS; 71.9% (277) in the 10th RS and 85.2% (416) in the 17th Regional. Regarding the guidelines on the advantages of exclusive breastfeeding, all regionals obtained a significant percentage in the “yes” answers, being 72.8% (289); 71.9% (277); 64.8% (316), respectively. About the correct grip orientation, breastfeeding on demand and the importance also a percentage of affirmative answers. Conclusion: The assistance to the newborn in the three Health Regions showed that there is care practice, including the nurse, who assists the mother in this period, corroborating the health promotion in the hospital environment.